The impact of the teaching of rthics in a Medical and Allied Health Sciences curriculum in International Islamic University Malaysia - Osman, Ariff; Muhammad, Siti Aeshah @ Naznin; Umar Ahmad, Kasule (Faculty of Medicine, International Islamic University Malaysia, 2008)
Background: The approach to the teaching of ethics and professionalism in the Faculty of Medicine (FM) of International Islamic University Malaysia (IIUM) is unique. A specifically designed package is incorporated designated as the Islamic Input into the Medical Programme (IIMP). The IIMP spans over the entire 5 years of the medical programme. In the Faculty of Allied Health Sciences (FAHS) students do not go through a similar Islamic Input module but exposed to ethical issues specific to health sciences. Method: The aim of this study is to assess the impact of the teaching of ethics through the IIMP. A cross-sectional study was conducted in medical and allied health sciences faculties of IIUM. In total 259 students volunteered and were allocated to 4 groups, Years 2 and 5 students of FM and Years 2 and 4 of FAHS. A set of questionnaire consisting of 20 vignettes related to medical ethics was distributed to all students. An independent t-test was used to compare the mean total scores between the groups. Results: A significant difference (p < 0.05) was seen between the mean total scores for the Year 2 and Year 5 students of FM; Year 2 students of FM and Year 2 students of FAHS; and between the Year 5 students of FM and Year 4 students of FAHS. Also there was significant difference between the two medical and allied health sciences groups as a whole. Discussion: This study suggests that the IIMP of the IIUM has a positive impact on the medical students when dealing with ethical issues. The Year 5 medical students were expected to have obtained a higher mean total score. The probable reason for the lower mean total score include the teaching-learning approach utilized which is mainly lecture with minimal small group approach. Also the allocation of marks for medical ethics in summative assessment in the IIUM medical curriculum is minimal compared to the core medical subjects which would have some influence on the weight given by students. Conclusion: The Medical Faculty of IIUM believes that the approach to the teaching of medical ethics by incorporating the Islamic Input module is effective, practical and relevant. However the teaching-learning method and the assessment will have to be re-addressed to achieve greater impact.